White blood cells in pregnancy: reference intervals for before and after delivery - Samuel Dockree (Elsevier, 2021)
Background: White blood cells (WBC) are commonly measured to investigate suspected infection and inflammation in pregnant women, but the pregnancy-specific reference interval is variably reported, increasing diagnostic uncertainty in this high-risk population. It is essential that clinicians can interpret WBC results in the context of normal pregnant physiology, given the huge global burden of infection on maternal mortality. Methods: We performed a longitudinal, repeated measures population study of 24,318 pregnant women in Oxford, UK, to map the trajectory of WBC between 8-40 weeks of gestation. We defined 95% reference intervals (RI) for total WBC, neutrophils, lymphocytes, eosinophils, basophils, and monocytes for the antenatal and postnatal periods. Findings: WBC were measured 80,637 times over five years. The upper reference limit for total WBC was elevated by 36% in pregnancy (RI 5.7-15.0×109/L), driven by a 55% increase in neutrophils (3.7-11.6×109/L) and 38% increase in monocytes (0.3-1.1×109/L), which remained stable between 8-40 weeks. Lymphocytes were reduced by 36% (1.0-2.9×109/L), while eosinophils and basophils were unchanged. Total WBC was elevated significantly further from the first day after birth (similar regardless of the mode of delivery), which resolved to pre-delivery levels by an average of seven days, and to pre-pregnancy levels by day 21. Interpretation: There are marked changes in WBC in pregnancy, with substantial differences between cell subtypes. WBC are measured frequently in pregnant women in obstetric and non-obstetric settings, and results should be interpreted using a pregnancy-specific RI until delivery, and between days 7-21 after childbirth. Funding: None.